Application of Box-Behnken design to formulate and optimize multipolymeric fast dissolving film of rizatriptan benzoate (Asian Journal of Pharmaceutics (AJP), 2014)
The present investigation aims at formulation and optimization of multipolymeric fast dissolving film of rizatriptan benzoate.Three film forming polymers namely hydroxypropyl methylcellulose (HPMC), maltodextrin and polyvinylalcohol wereexplored using Box-Behnken experimental design to derive optimized fast dissolving film formulation using desirability function.Analysis of variance (ANOVA) was performed for five dependent variables tensile strength, folding endurance, load at yield,percentage elongation and percentage drug release in 30 s (Q30). Mathematical regression equations were derived by applyingANOVA and validated using checkpoint batches. Results of the experimental design exposed that the effect of independentfactors HPMC and maltodextrin significantly influenced the mechanical properties and percentage drug release from thefilm. Optimized batch was derived based on set criteria using desirability function. Reponses of the optimized formulationwere tensile strength (500 N/m2), folding endurance (203), load at yield (15.06 N/m2), percentage elongation (4.56%) andQ30 (60.03%) falling under acceptable limits. High percentage drug release from the film in simulated saliva and simulatedgastric fluid reveal fast dissolving characteristics. Fast dissolving dosage form can help patients with diseases like migraine